Photo‐Induced C−H Methylation Reactions - Li, Qian‐Yu; He, Yuhang; Lin, Yu‐Mei; Gong, Lei (Chemistry : a European journal, 2023)
Direct C−H methylation is a highly valuable approach for introducing methyl groups into organic molecules, particularly in pharmaceutical chemistry. Among the various methodologies available, photo‐induced methylation stands out as an exceptional choice due to its mild reaction conditions, energy efficiency, and compatibility with functional groups. This article offers a comprehensive review of photochemical strategies employed for the direct and selective methylation of C(sp3)−H, C(sp2)−H, and C(sp)−H bonds in various organic molecules. The discussed methodologies encompass transition‐metal‐based photocatalysis, organophotocatalysis, as well as other metal‐free approaches, including electron donor‐acceptor (EDA)‐enabled transformations. Importantly, a wide range of easily accessible agents such as tert‐butyl peroxide, methanol, DMSO, methyl tert‐butyl ether, TsOMe, N‐(acetoxy)phthalimide, acetic acid, methyl halides, and even methane can serve as effective methylating reagents for modifying diverse targets. These advancements in photochemical C−H methylation are anticipated to drive further progress in the fields of organic synthesis, photocatalysis, and pharmaceutical development, opening up exciting avenues for creating novel organic molecules and discovering new drug compounds. In this review, we present a concise overview of recent breakthroughs in photochemical C−H methylation. These advancements encompass a variety of methodologies, including transition metal‐based photocatalysis, organophotocatalysis, and various metal‐free approaches, such as electron donor‐acceptor ‐enabled processes.